Suprapubic bladder hernia: about a case - Croci, Fabio; Gastambide, Carmelo; Terra, Eneas; Durante, Arturo (Cirugía del Uruguay, 1983)
The au thors presen t one case of suprapu bic med ial bladder hernia in a patient who had been prev iously operated on bilateral inguinal hernia. The preoperative d iagnosis could only be made by means of a retrograde urethrocystoscopy; being this a very rare situation. The pathogenesis of the hernia is discussed.